Religious Moderation Based on Ancient Manuscript in Maros District - Wardiah Hamid; Hamsiati Hamsiati; Idham Idham; Wan Shahrazad Wan Sulaiman (Balai Penelitian dan Pengembangan Agama Semarang, 2023)
The harmony movement in Indonesia has been carried out by the nation's predecessors. The remains of ancient manuscripts in Maros, South Sulawesi, are historical evidence that religious moderation has been practiced. This article aims to examine the practice of religious moderation in the Lontaraq Manuscript of Kassi, Labuang, Pacelle. Through the philological method, this study found the following findings. First, these manuscripts express historical events in the past which have very strong nuances of religious moderation in them. Slavery and extortion were commonplace at that time, but there were breakthroughs or efforts made by Karaeng to abolish slavery and extortion at that time. The breakthrough is through humanity, justice, equality of social strata, and love between the people and the authorities. Equality without caste strata is in line with the justice proclaimed in Religious Moderation. Second, differences in ethnicity, language, and religion become social forces with a culture of mutual respect.